ANALYSIS OF GOLDFISH PRODUCTION EFFICIENCY (CASE STUDY: LAWE BULAN SUBDISTRICT SOUTHEAST ACEH DISTRICT) - Intan Mulia; Rulianda P Wibowo; Rahmanta (CV. Radja Publika, 2023)
Goldfish is in great demand by the people of Southeast Aceh because it is easily obtained in the market and becomes a typical dish. There is an increase in feed prices while output prices are fixed. So many farmers stopped producing but some survived. There is a difference in productivity between farmers who quit and farmers who stay. Farmers must improve production efficiency with the use of the right inputs so as to minimize costs and maximize profits. The study was conducted in Lawe Bulan District with the number of samples used as many as 40 farmers. The analysis used by DEA (Data Envelopement Analysis) to obtain Technical, Allocative and Economic Efficiency values and Tobit Regression Analysis to see the relationship between efficiency and farmer characteristics. The results of the DEA Analysis obtained a technical efficiency value of 0.757 or 75.5%. The allocative efficiency value was obtained at 0.919 or 91.9%. The Economic Efficiency Rate is 0.832 or 83.2%. The results of Tobit Regression are technically significantly positively related to the age of farmers. Allocative efficiency revealed a significant effect at the level of 5% and negatively related between allocative efficiency and education level. The results of the DEA analysis of the level of production efficiency have not been efficient. The Technical Efficiency score has an inefficiency of 24.5%. The allocative efficiency value of inefficiency was 8.1%. The Economic Efficiency score of inefficiency was 16.8%. The results of tobit regression there are sources of inefficiency of socioeconomic variables that become inefficienciesSuch as technical efficiency of education and number of dependents, allocative efficiency of age, education and experience, economic efficiency of experience variables and number of dependents.